Pendekatan Metodologi Studi Islam terhadap Isu Lingkungan Global dalam Kerangka Tujuan Pembangunan Berkelanjutan (SDGs) - Najwa Salsabila Agustina; Rafiq Alim Ramadhan; Habibi Ramadhan; Abdul Fadhil (Advances In Education Journal, 2025)
The modern ecological crisis, characterized by climate change and natural resource exploitation, demands a holistic approach integrating science with spiritual values. This study aims to explain the environmental concept in Islam, examine Islamic study methodologies regarding ecological issues, and analyze the integration of Islamic values in supporting the Sustainable Development Goals (SDGs). The research method employed is library research with a descriptive-analytical approach toward contemporary scientific literature. The results indicate that Islam offers a comprehensive ecological framework through the principles of tawhid, khalifah, and mīzān. This study finds that the integration of Islamic values into the SDGs is practically implemented through eco-pesantren models, eco-mosques, and green economic instruments such as Green Sukuk. In conclusion, the environmental crisis is a manifestation of moral degradation requiring spiritual restoration through appropriate Islamic methodological approaches. The impact of this research reaffirms that engaging religious values can strengthen collective ecological awareness and accelerate the achievement of the global sustainable development agenda.